Collective Action-A Challenge and an Opportunity for Water Governance - Maria Manuela Castro Silva (European Regional Science Association (ERSA), 2006)
This paper addresses the motivations that drive participation in groups concerning water protection and provides a review of the key role collective action plays in accessing and managing water resources. It also analyses the conditions and factors which make such organizations effective in solving shared problems and in faciliting and institutionalizing negotiation platforms. Collective action heavily relies on the social capital existing in a community to accomplish goals and objectives. These social networks allow for flow of information, serving not only to criticize but also to purpose a different course in environmental and particularly, water management. The vital role of collective action and other "major groups" in sustainable development was recognized in Chapter 27[2] of Agenda 21, leading to revised arrangements for consultative relationship between the United Nations and non-governmental organizations which are, indeed, collective voluntary action. The coalition building capacity suggesting the mobilization of civil society in the sense of organized interests can supplement the ultimate responsibility of the traditional democratic institutions according to the implementation of the Aarthus Principles. Modern governance calls for consensus, seeking processes with organized interests, a good culture of consultation and participation. Collective action meets these goals, as offers the chances for environmental effectiveness, contributing to information generation and creation of relevant knowledge. These factors may relieve the legislator, affecting the way in which powers are exercised at European level, particularly as regards the five principles of good governance, namely openness, participation, accountability, effectiveness and coherence. Most problems with water resource management are felt at the lowest levels and changes in water management are required down to the individual action, reasons why the development strategies call for extensive pro-active participation (at different levels, sectors and scales) upholding the principles of subsidiarity. Finally, this paper also highlights the role performed by collective action in increasing advocacy skills and capacity, contributing to strengthening governance at the local level through favoring the enabling environment for water protection and conservation.
Keywords: 330